Crohn's disease: A retrospective analysis between computed tomography enterography, colonoscopy, and histopathology. Issue 4 (November 2019) - Saade, C.; Nasr, L.; Sharara, A.; Barada, K.; Soweid, A.; Murad, F.; Tawil, A.; Ghieh, D.; Asmar, K.; Tamim, H.; Khoury, N.J.
Abstract: Introduction: To investigate the spectrum of computed tomography enterography (CTE) findings of active Crohn's disease (CD) in comparison to endoscopic, histopathologic and inflammatory markers. Methods: Hospital records of 197 patients with known or suspected CD who underwent CTE over a period of 5 years were reviewed. Eighty-nine patients fulfilled the inclusion criteria. Three-point severity scores for endoscopy, pathology, and haematologic inflammatory markers were recorded. The findings on CTE were identified by three readers and correlated with endoscopic, pathologic, and haematologic severity scores. Statistical analysis was carried out employing a Pearson Chi square test and Fisher exact test. Receiver operating characteristic (ROC), visual grading characteristic (VGC) and Cohens' kappa analyses were performed. Results: The CTE findings which were significantly correlated with the severity of active disease on endoscopy include bowel wall thickening, mucosal hyperenhancement, bilaminar stratified wall enhancement, transmural wall enhancement, and mesenteric fluid adjacent to diseased bowel (p < 0.05). Only bowel wall thickening and bilaminar stratified wall enhancement correlated with the pathological severity of active CD. ROC and VGC analysis demonstrated significantly higher areas under the curve (p < 0.0001) together with excellent inter-reader agreement (k = 0.86). Conclusion: CTE is a reliable tool for evaluating the severity of active disease and helps in the clinical decision pathway. Highlights: Crohn's disease (CD) has recurrent exacerbations requiring frequent monitoring. No association between CTE findings and inflammatory blood markers were found. CTE is superior for longitudinal CD monitoring.